Fatty liver index and hypertension-mediated organ damage in never-treated hypertensive patients without diabetes mellitus. Issue 12 (December 2021) - Siafi, Eirini; Andrikou, Ioannis; Konstantinidis, Dimitris; Kakouri, Niki; Iliakis, Panagiotis; Koskinas, John; Koullias, Emmanouil; Thireos, Eleftherios; Tousoulis, Dimitris; Thomopoulos, Costas; Tsioufis, Costas
Abstract : Background: We investigated whether fatty liver index (FLI), a surrogate marker of nonalcoholic fatty liver disease (NAFLD), is associated with hypertension-mediated organ damage (HMOD) in never-treated hypertensive patients without diabetes mellitus. Methods: We performed both clinic and ambulatory blood pressure (BP) measurements, and calculated the FLI for all participants. A FLI of no less than 60 indicates a high-risk of underlying NAFLD, whereas a FLI of less than 60 indicates lower risk. We evaluated left ventricular mass (LVM) by echocardiography, arterial stiffness by carotid--femoral pulse wave velocity (PWV), capillary rarefaction by nailfold capillaroscopy, as well as urinary albumin-to-creatinine ratio (ACR). HMOD was defined according to the categorical thresholds for each domain, except for capillary rarefaction in which case the categorization of patients was made by the median. Results: We included 146 hypertensive patients (men, 43.8%; mean age, 56.6 ± 10.8 years; BMI, 30.3 ± 4.9 kg/m 2 ; FLI, 57.2 ± 27.7; office, systolic/diastolic, and 24-h BP, 153.5 ± 15.8/94.7 ± 9.8 mmHg, and 140.5 ± 9.9/83.8 ± 9 mmHg, respectively). Patients with FLI at least 60 ( n  = 76) were younger, with higher BMI and 24-h SBP, compared with patients with FLI less than 60 ( n  = 70). FLI was associated with HMOD after adjustment (LVM indexed to height, P  = 0.004; PWV, P  = 0.047; reduced capillary density, P  = 0.001; and logACR, P  = 0.003). High-risk FLI phenotype and FLI z scores increased the likelihood of any HMOD by 3.8 (95% confidence interval, 1.6–7.1) and 5.4 (95% confidence interval, 2.3–15.0) times, respectively. However, the increased number of HMOD domains has progressively stopped being determined by the FLI z scores ( P  = 0.65). Conclusion: High-risk FLI pattern was associated with various HMOD, and may re-classify never-treated hypertensive patients without diabetes mellitus into a higher cardiovascular risk level. Abstract : Supplemental Digital Content is available in the text